ENFORCEMENT OF SOLID WASTE MANAGEMENT LAWS AND PUBLIC HEALTH OUTCOMES IN URBAN SOUTHEAST NIGERIA - KELECHI GOODLUCK ONYEGBULE, PHD , ODOH BEN URUCHI, PHD , EMMANUEL OKPARA , NNAEMEKA B. AMADI, PHD (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This qualitative study examines why robust solid waste management laws consistently fail to protect public health in the rapidly urbanising cities of Southeast Nigeria (Enugu, Onitsha, and Aba). Drawing on 72 in-depth interviews, six focus groups, and 180 hours of participant observation, four interlocking themes emerged: the theatre of enforcement (laws brandished but never applied), jurisdictional musical chairs (endless buck-passing between federal, state, and local agencies), the politics of the belly (systematic diversion of resources through patronage and corruption), and the slow violence of waste (gradual, embodied harm experienced as poisoned water, chronic respiratory illness, and recurrent epidemics among the urban poor). These findings reveal enforcement failure not as technical incapacity but as deliberate political subversion. Comparative analysis with Ghana, Kenya, India, Indonesia, Brazil, and Mexico shows the same dynamics recur globally wherever informal institutions of power override formal statutes. The study concludes that meaningful change requires depoliticising enforcement, clarifying responsibilities, ring-fencing revenue, professionalising officers, and integrating informal waste workers into participatory governance structures.